ANALISIS PERBEDAAN TIPE KEPRIBADIAN A DAN B TERHADAP MANAJEMEN KONFLIK INTERPERSONAL PADA PEGAWAI RUMAH SAKIT KHUSUS MATA PROVINSI SUMATERA SELATAN - Baharudin Baharudin; Fauziah Nuraini Kurdi; Andries Lionardo (Psikis : Jurnal Psikologi Islami, 2015)
Hospital as one of  health public services institution on delivering health services supported by multidiscipline professions that have diversity of personality. Personality is one of factor contributed in triggering interpersonal conflict at workplace. There are five interpersonal conflict managements commonly used, namely ; integrating, obliging, dominating, avoiding dan compromising. Research was conducted on March 2015 at Eye Specialist Hospital South Sumatera Province which 75 respondens as samples of the reaserch. The objectives of this reaserch to explore differences among type A and B personality toward interpersonal conflict management in the hospital.  Cross Sectional Study  as design of the reaserch with Manova and Post Hoc test analyisis. From this reaserch found that  type A personality is dominant personality of employee, and dominant interpersonal conflict management is integrating style. Based on the risult of Post Hoc analysis  shown that significant difference between type A and B personality towrad management conflict of  interpersonal found on obliging style with P value 0,000 < 0,05, for other management conflict style  was not found.